Computational fatigue assessment of mooring chains under tension loading. (December 2019) - Martinez Perez, Imanol; Constantinescu, Andrei; Bastid, Philippe; Zhang, Yan-Hui; Venugopal, Vengatesan
Abstract: This paper presents a computational fatigue assessment method of mooring chains under tensile loading, it is composed of a mechanical analysis followed by a fatigue analysis. The mechanical analysis is performed in two steps: residual stress prediction and service loading. From this analysis, the shakedown cycle is extracted at the critical points, ie: the asymptotically stabilized stress-strain cycles. As the mooring chain under service loading is under elastic shakedown, the Dang Van fatigue criterion is applied for the fatigue analysis. The accuracy of the proposed fatigue assessment method is proved by comparing with the experimental results from full-scale fatigue testing of mooring chain in seawater. The numerical results match both the experimental observations with respect to the localization of the damage zone and the lifetime. Highlights: Computational fatigue assessment of mooring chains accounting for residual stresses The methodology proposed accounts for phenomena that is not covered by engineering standards for fatigue analysis for mooring chains. The predicted fatigue lifetimes have been compared with experimental data obtained from full scale fatigue testing